State of the art biofabrication technologies and materials for bone tissue engineering. Issue 3 (14th August 2018) - Pereira, Taciana; Prendergast, Margaret E; Solorzano, Ricky
Bone tissue engineering is a field whose relevance is paramount, especially for the treatment of musculoskeletal-related disabilities. Failure of conventional methods to create physiologically relevant bone materials has prompted exploring several 3D-printing and additive manufacturing processes, including bioprinting, selective laser sintering, electrospinning and stereolithography. These technologies emerged in conjunction with new materials such as Hyperelastic Bone™, graphene and thermoplastics coupled with cell-laden hydrogels. This work will review these current state-of-the-art materials and technologies, their impact on advancements in bone tissue engineering and will highlight future considerations for the field.